Pelvic Actinomycosis Mimicking Ovarian Malignancy Causing Unilateral Hydronephrosis - Cemil Kaymaz; Bahadır Saatlı; Özgür Bige; Meral Koyuncuoğlu; Aykut Kefi; Uğur Saygılı (Medical Network, 2007)
Pelvic actinomycosis is a chronic granulomatous suppurative disease caused by actinomyces israelii and usually associated with long-standing use of an intrauterine device. Pelvic actinomycosis can cause tuboovarian abscess, ureteral and bowel obstruction in some rare cases mimicking an ovarian tumor. We report a pelvic actinomycosis case with elevated Ca 125 level and obstructed ureter mimicking an ovarian tumor. The preoperative imaging methods and Ca 125 level indicated an ovarian malignancy, but frozen section diagnosis was benign, and overtreatment was avoided. Pelvic actinomycosis, although is a rare granulomatous suppurative disease, in case of long-standing use of an intra-uterine device and ovarian mass, it should be in the mind of the surgeon as a differential diagnosis to avoid excessive surgery.